2014
DOI: 10.1136/bmj.g93
|View full text |Cite
|
Sign up to set email alerts
|

Presumed safe no more: lessons from the Wingspan saga on regulation of devices

Abstract: Despite a randomized controlled trial showing clear safety concerns with the Wingspan intracranial stent system, the device remains on the market. Ari J Gartenberg and colleagues argue that the exemption system used to obtain its market approval in the US is not adequate for high risk devices

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…40 In order to be considered for this exemption, comparable devices must not be available through any other FDA pathway; the device must not pose an "unreasonable risk of illness or injury;" and its "probable benefit must outweigh its risks." 41 The 21st Century Cures Act of 2016 expanded the limits of this program: Currently, devices eligible for this exemption should be intended to treat or diagnose diseases or conditions affecting no more than 8,000 U.S. patients (an increase from the previous 4,000-patient limitation). 42 As part of the assessment for these devices, the FDA is to consider the target patient population and size, as well as the device's intended use and existing treatment options.…”
Section: E Humanitarian Devicesmentioning
confidence: 99%
“…40 In order to be considered for this exemption, comparable devices must not be available through any other FDA pathway; the device must not pose an "unreasonable risk of illness or injury;" and its "probable benefit must outweigh its risks." 41 The 21st Century Cures Act of 2016 expanded the limits of this program: Currently, devices eligible for this exemption should be intended to treat or diagnose diseases or conditions affecting no more than 8,000 U.S. patients (an increase from the previous 4,000-patient limitation). 42 As part of the assessment for these devices, the FDA is to consider the target patient population and size, as well as the device's intended use and existing treatment options.…”
Section: E Humanitarian Devicesmentioning
confidence: 99%
“…Moreover, the exact nature of FDA action after completion of the PAS and 522 studies is also not routinely disseminated. Gartenberg et al 10 demonstrated how the FDA did not remove the Wingspan intracranial stent system from market in 2012 despite postapproval data suggesting significantly high stroke and mortality risks. Instead, the FDA reformed the indications for the device and ordered a 522 study for the device, which is still pending.…”
Section: Postapproval Surveillance Strategiesmentioning
confidence: 99%
“…Instead, the FDA reformed the indications for the device and ordered a 522 study for the device, which is still pending. 10 The most common result from a PAS completed study is a labeling change of the studied device, which has been ordered for 31 studies to date. 31 …”
Section: Postapproval Surveillance Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, devices deployed in tortuous arteries show various levels of twisting. The development of repositionable stent-grafts has reduced this issue, but has not fully eliminated it [45,46]. Twisting in stent-grafts must be studied because indications of incontinence at the site of the twists have been observed in explants.…”
Section: Introductionmentioning
confidence: 99%